PENGARUH KARAKTERISTIK IBU BALITA, FAKTOR PEMUDAH DAN PENGUAT TERHADAP PEMBERIAN IMUNISASI DASAR LENGKAP PADA BAYI DI WILAYAH KERJA PUSKESMAS PIJORKOLING KECAMATAN PADANGSIDIMPUAN TENGGARA - Eva Yusnita Nasution; Wiwi Wardani Tanjung (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Immunization is an effort of giving immunity on infants and children by incorporating the vaccine into the body so that the body makes antibodies to prevent certain diseases. The achievement of fully immunized target based on by National data is around 80-90%, while the achievement of immunization in Padangsidimpuan in 2014 by 47.1% and in Pijorkoling Health Centre in 2014, BCG immunization was obtained 49.5%, DPT / HB3 immunization was obtained 27.6%, polio immunization was obtained 32,4% and measles immunization was obtained 29,3%. The objective of this study is to determine and analyze the influence of the characteristics of mothers (work and parity), predisposing factors (knowledge and belief) and reinforcing (husband's support and the support of health professionals) to complete basic immunization on infants in sub-district Puskesmas Pijorkoling Southeast Padangsidimpuan. This type of research used analytic study with cross sectional approach. The population of this study was all mothers who have infants with sampling proportional sampling technique with a total sample of 81 respondents. Data were collected through medical records and interviews used questionnaires. Data was analyzed by univariate, bivariate used Chi-Square test at the 95% confidence level (p <0.05) and multivariate used logistic regression test. The results showed that the relationship with p value 0.036 and the support of a husband with a p value of 0.001 against the complete basic immunization on infants. In this study, the relationship of parity with p value 0.180 and the support of health professionals with p value 0.377 to complete basic immunization on infants was not found. The influence of knowledge with p value 0.001 and the value of Exp (B) 17.523 and trust with p value 0.044 and the value of Exp (B) 4.460 to complete basic immunization in infants was affected. It is suggested to the workers of Pijorkoling health center to provide counseling persuasion in improving the knowledge and encourage the mothers to give the complete basic immunization on infants. Thus the achievement of immunization target is more increasing.